INVESTIGATING THE PATH LOSS OF CELLULAR MOBILE NETWORK IN SUBURBAN AREAS OF BENIN METROPOLIS OF NIGERIA AT 910MHZ - Akhideno, Itua O.; Eguasa, Omo (FUDMA JOURNAL OF SCIENCES, 2023)
This paper focuses on investigating path loss of mobile cellular network in suburban areas of Benin metropolis at a propagation frequency of 910MHz. The network Cell Info Lite application installed in GIONEE M5 CDMA was used to measure the received signal strength of the transmitted signal. The relative parameters were obtained from 100meters from the Glo base station from August, 2021 to October, 2021 within an average temperature of 270C. The results showed that Hata models are extensively used for the analysis of path loss evident in mobile cellular networks, GSM and CDMA system as depicted by the terrain of sub-urban areas of Benin City Metropolis. It was observed that the more the mobile stations move away from the base station, the higher the signal loss. This paper therefore guides cellular network service provider on accurate method of designing, deploying, and managing network to enhance good network coverage.
Keywords: Hata model; GSM (Global System of Communication; CDMA(Wireless Code Division Multiple Access Systems; Long Term Evolution (LTE)